On Capability-Based Requirements of Vocational Curriculum Development (Asian Education Studies, 2022)
Since the competency-based curriculum was introduced into China in the early 1990s, it has adapted to the institutional development of our country and achieved unprecedented development. In the course of competency-based curriculum implementation, we encounter the crisis of knowledge based, especially human-oriented curriculum view. But today, the aptitude -based curriculum concept is still the main guiding ideology of curriculum development in vocational colleges. This is because vocational education aptitude standard has the stipulation to the vocational curriculum development. This paper will discuss its regulation.